Revisiting the systematics of the Leptodactylus melanonotus group (Anura: Leptodactylidae): Redescription of L. petersii and revalidation of its junior synonyms - Gazoni, Thiago [UNESP]; Lyra, Mariana L. [UNESP]; Ron, Santiago R.; Strussmann, Christine; Baldo, Diego; Narimatsu, Hideki [UNESP]; Pansonato, Andre; Schneider, Rosio G.; Giaretta, Ariovaldo A.; Haddad, Celio F. B. [UNESP]; Parise-Maltempi, Patricia P. [UNESP]; Carvalho, Thiago R. [UNESP] (Elsevier B.V., 2021)
The Leptodactylus melanonotus species group is widely distributed across the Neotropics and contains 17 valid species. Here we reassess the taxonomic status of several taxa of the group, focusing mainly on the Amazonian L. petersii and both its junior synonyms (L. brevipes and L. intermedius), based on morphological, acoustic, cytogenetic, and DNA sequence data. The phylogenetic analyses recovered a monophyletic L. melanonotus group. However, L. petersii in the broad sense was found to be polyphyletic by containing the nominal species and two other lineages more closely related to L. podicipinus than to L. petersii. Color patterns and calls also support the distinctiveness among these lineages. Moreover, one of the lineages (L. brevipes) has a unique karyotype in the genus (2n = 20 vs. 2n = 22 in the other species). The holotype of L. petersii is presumably lost and a previous designation of a neotype was later considered as invalid. Therefore, we designate a new neotype for L. petersii and redescribe the species from the upper Negro River drainage. Also, we revalidate and characterize L. brevipes and L. intermedius from their type localities. Our study contributes to the systematics, cytogenetic and phenotypic variation, and distribution patterns of leptodactylid frogs in South America. (c) 2020 Elsevier GmbH. All rights reserved.
Keywords: Bioacoustics; Biodiversity; Cytogenetics; Leptodactylinae; Molecular systematics; Neotropics